A novel liposome adjuvant DPC mediates Mycobacterium tuberculosis subunit vaccine well to induce cell-mediated immunity and high protective efficacy in mice. Issue 11 (8th March 2016) - Liu, Xun; Da, Zejiao; Wang, Yue; Niu, Hongxia; Li, Ruiying; Yu, Hongjuan; He, Shanshan; Guo, Ming; Wang, Yong; Luo, Yanping; Ma, Xingming; Zhu, Bingdong
Highlights: We constructed a novel adjuvant composed of dimethyl dioctadecylammonium (DDA), Poly I:C and cholesterol (DPC for short). The results showed that the DPC adjuvant with particle size of 400 nm and zeta potential of 40 mV was in good stability. The adjuvant of DPC with fusion protein LT70 generated strong antigen-specific humoral and cell-mediated immunity. The adjuvant of DPC with fusion protein LT70 generated strong cell-mediated immunity and high protective efficacy against TB. Abstract: Tuberculosis (TB) is a serious disease around the world, and protein based subunit vaccine is supposed to be a kind of promising novel vaccine against it. However, there is no effective adjuvant available in clinic to activate cell-mediated immune responses which is required for TB subunit vaccine. Therefore, it is imperative to develop new adjuvant. Here we reported an adjuvant composed of dimethyl dioctadecylammonium (DDA), Poly I:C and cholesterol (DPC for short). DDA can form a kind of cationic liposome with the ability to deliver and present antigen and can induce Th1 type cell-mediated immune response. Poly I:C, a ligand of TLR3 receptor, could attenuate the pathologic reaction induced by following Mycobacterium tuberculosis challenge. Cholesterol, which could enhance rigidity of lipid bilayer, is added to DDA and Poly I:C to improve the stability of the adjuvant. The particle size and Zeta-potential of DPC were analyzed in vitro . Furthermore, DPC was mixed with a TB fusion protein ESAT6-Ag85B-MPT64(190-198)-Mtb8.4-Rv2626c (LT70) to construct a subunit vaccine. The subunit vaccine-induced immune responses and protective efficacy against M. tuberculosis H37Rv infection in C57BL/6 mice were investigated. The results showed that the DPC adjuvant with particle size of 400 nm and zeta potential of 40 mV was in good stability. LT70 in the adjuvant of DPC generated strong antigen-specific humoral and cell-mediated immunity, and induced long-term higher protective efficacy against M. tuberculosis infection (5.41 ± 0.38 log10  CFU) than traditional vaccine Bacillus Calmette–Guerin (BCG) (6.01 ± 0.33 log10  CFU) and PBS control (6.53 ± 0.26 log10  CFU) at 30 weeks post-vaccination. In conclusion, DPC would be a promising vaccine adjuvant with the ability to stimulate Th1 type cell-mediated immunity, and could be used in TB subunit vaccine.